Yield of Head Imaging in Ambulatory and Hospitalized Patients With SARS-CoV-2: A Multi-Center Study of 8675 Patients. (July 2021) - Greenway, Melanie R. F.; Erben, Young; Huang, Josephine F.; Siegel, Jason L.; Lamb, Christopher J.; Badi, Mohammed K.; Sakusic, Amra; Gopal, Neethu; Meschia, James F.; Lin, Michelle P.
Background and Purpose: To describe the neurological and cerebrovascular findings in patients who tested positive for SARS-CoV-2 and underwent head imaging in ambulatory and inpatient settings. Methods: Consecutive patients aged ≥18 years with SARS-CoV-2 infection diagnosed or treated at Mayo Clinic sites from 3/11/2020 to 7/23/2020 with head CT or brain MRI within 30 days of SARS-CoV-2 diagnosis were included. Demographics, medical history, indication for SARS-CoV-2 testing, neurologic symptoms, indication for brain imaging, neuroimaging findings, etiology of cerebrovascular events, and hospital course were abstracted from medical records. Results: Of 8, 675 patients with SARS-CoV-2, 180 (2.07%) had head imaging. Mean age of the entire cohort was 42 ± 18 years, whereas mean age of those with head imaging was 62 ± 19 years. Common indications for imaging were headache (34.4%), encephalopathy (33.4%), focal neurologic symptom (16.7%), and trauma (13.9%). While 86.1% of patients who underwent head imaging had normal exams, cerebrovascular events occurred in 18 patients (0.21% of the total cohort). Of patients with cerebrovascular events, 8 (44.5%) had acute infarct; 6 (33.3%), acute intracranial hemorrhage; 5 (2.8%), subacute infarct; and 1 (0.6%) posterior reversible encephalopathy syndrome. In the thirteen patients with ischemic stroke, 6 (46.2%) had cryptogenic stroke; 3 (23.1%), other defined causes; 2 (15.4%), small vessel stroke; 1 (7.7%), large vessel stroke; and 1 (7.7%) cardioembolic stroke. Conclusion: In ambulatory and hospitalized patients with SARS-CoV-2 infection, the rate of head imaging is low, with common indications of encephalopathy and headache. Cerebrovascular events occurred rarely, and cryptogenic stroke was the most common stroke mechanism.